(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2024)
This paper uses hybrid sliding mode control to solve an output feedback tracking problem for the induction motor (IM). The main idea of this approach lies in the design of a law that ensures a smooth transition between two sliding regimes based on the choice of two sliding surfaces, one being linked to the other. The control is a combination of first and second-order sliding modes. The proposed approach controls the speed and rotor flux amplitude of the induction motor and guarantees the stability of the decoupled speed and rotor flux by using a Lyapunov method. The hybrid sliding mode algorithm provides robustness despite external disturbances and parameter variations. The controller has been implemented on an experimental setup, and results are presented to confirm the proposed method’s effectiveness, robustness, and good performance.